2000
DOI: 10.1002/1529-0131(200007)43:7<1478::aid-anr10>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Determining minimally important changes in generic and disease-specific health-related quality of life questionnaires in clinical trials of rheumatoid arthritis

Abstract: Based on these results, minimally important changes in the SF-36 scales and HAQ disability scores were determined, which will be useful in interpreting HQL results in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
228
3
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(263 citation statements)
references
References 21 publications
(16 reference statements)
13
228
3
12
Order By: Relevance
“…Self-efficacy has been correlated with SLE outcome in several studies (8)(9)(10)(11)(12)(13)(14)(15) and has been found to consistently predict health-related outcomes in prospective studies (60). In this trial, we demonstrated that self-efficacy could be enhanced by our intervention and that it was a key predictor of mental health status and fatigue outcomes.…”
Section: Discussionmentioning
confidence: 52%
“…Self-efficacy has been correlated with SLE outcome in several studies (8)(9)(10)(11)(12)(13)(14)(15) and has been found to consistently predict health-related outcomes in prospective studies (60). In this trial, we demonstrated that self-efficacy could be enhanced by our intervention and that it was a key predictor of mental health status and fatigue outcomes.…”
Section: Discussionmentioning
confidence: 52%
“…The comparison of patients on ERT and patients naïve to ERT revealed that bodily pain was the only domain whose score had a statistically significant difference between groups (p ¼ 0.036), and the higher scores were found to be for the ERT group. According to the criteria established by Kosinski et al (2000), this change may also be classified as clinically significant. The physical functioning, role-physical, general health, social functioning, and role-emotional domains also showed clinically significant changes that favored the ERT subgroup (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in domain scores were classified as clinically significant according to the study conducted by Kosinski et al (2000), who evaluated patients with rheumatoid arthritis in the USA. The minimally significant changes defined by those authors were as follows: physical functioning -8.4; role-physical -21.0; bodily pain -14.7; general health -4.2; vitality -11.1; social functioning -11.7; roleemotional -17.9; and mental health domain -7.3.…”
Section: Definition Of Clinically Significant Changementioning
confidence: 99%
“…At baseline, median Sharp/van der Heijde scores were already larger in PROAR cohort patients than in SERAP cohort patients, and the progression rate was double in the nonintervention group (Table 1). The median TSS (25th percentile, 75th percentile) of PROAR cohort patients worsened from 12 (6,20) at baseline to 21 (11,28) after 2 years (P Ͻ 0.001). The same happened in the SERAP cohort, with the median TSS (25th percentile, 75th percentile) worsening from 7 (3,18) to 13 (5, 25) after 2 years (P ϭ 0.033).…”
Section: Resultsmentioning
confidence: 99%